![(3x + y)(2x - 3) + (5x - 4)(x + 2) (3x + y)(2x - 3) + (5x - 4)(x + 2)](https://tex.z-dn.net/?f=%283x+%2B+y%29%282x+-+3%29+%2B+%285x+-+4%29%28x+%2B+2%29)
Answers
Answered by
1
Answer:
K I am done
The Pic is the answer
Attachments:
![](https://hi-static.z-dn.net/files/dd4/88ad29bf39f8c4adf18d3483ee14d38a.jpg)
Answered by
0
Step-by-step explanation:
6x-9x+8x-12=5x+10x-4x-8
6x-9x+8x-12=5x+10x-4x-816x =-24
6x-9x+8x-12=5x+10x-4x-816x =-24x=-24/16
6x-9x+8x-12=5x+10x-4x-816x =-24x=-24/16x=-15
Similar questions